THE COMMUNICATION FUNCTION COVERED IN GAN KIM YONG’S SPEECH ON RESPONSE TO CORONA VIRUS - Natalia Anggrarini; Deuis Dian Rosdiana (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2020)
This research deals with how the language used in communication, especially in the form of speech. It addresses to describe the criteria and categories within utterances as well as the communication function of speech. The speech acts theory used in this research is from Searle (1976). The data source of research is an English speech text addressed by Singapore Health Minister Gan Kim Yong delivered in parliament on the government's response to the coronavirus on February 3rd 2020. This research finds the representatives with 199 utterances (73%) as the most common speech acts which are followed by the other categories; directives in 21 utterances (13%), commissives in 19 utterances (12%) and expressive in 4 utterances (2%). The analysis finds the speaker has the intention to provide sufficient information about the 2019 novel coronavirus based on the preponderance of representatives which are indicated by the use of claiming, stating, reporting, asserting, and defining utterances that provide evidence about the real circumstances happened such as data, reasons, rationale, and explanation. Thus, the belief of speaker within utterances guides the listeners for being aware of the current conditions relates to the coronavirus.